Adapting and feasibility testing pre-registration e-learning resources for Professionalism in Osteopathy in the UK. Issue 1 (March 2015) - Browne, Fiona; Rolfe, Kerstin; Currie, Alan; Walker, Tim; Roff, Sue
Abstract: Background: The UK General Osteopathic Council (GOsC) has statutory duties of 'promoting high standards of education and training in osteopathy and keeping the provision of that training under review'. Students graduating from osteopathic educational institutions (OEIs) must meet the GOsC Osteopathic Practice Standards . 1 Objectives: One domain within the Osteopathic Practice Standards is 'professionalism'. Supporting guidance requires explicit teaching and learning opportunities about 'professionalism' in osteopathy. Our objectives are to establish the feasibility of adapting e-learning resources used widely in medical education to meet these requirements. Methods: A consensus group of two senior faculty representatives nominated by their Deans or Principals from each of the 11 UK OEIs and senior officers from the GOsC, with expertise in standards, reviewed and adapted the items of the two Dundee Polyprofessionalism resources used to explore professionalism in medical education. Four additional items were added. The agreed inventory was tested on two groups of 4 and 12 osteopathy students. Results: The adaptation and feasibility of 34 items for Professionalism in Osteopathy 1 (Academic) and the 45 items for Professionalism in Osteopathy 2 (Clinical) were agreed to explore professionalism in osteopathy. Conclusions: The Professionalism in Osteopathy e-learning resources will be field tested to explore their potential to guide learning and to track and help to benchmark the learning curve in pre-registration osteopathic professionalism.